Investigation of the intestinal trans-epithelial transport and antioxidant activity of two hempseed peptides WVSPLAGRT (H2) and IGFLIIWV (H3). (February 2022) - Bollati, Carlotta; Cruz-Chamorro, Ivan; Aiello, Gilda; Li, Jianqiang; Bartolomei, Martina; Santos-Sánchez, Guillermo; Ranaldi, Giulia; Ferruzza, Simonetta; Sambuy, Yula; Arnoldi, Anna; Lammi, Carmen
Graphical abstract: Highlights: Peptic hempseed peptides exert in vitro antioxidant activity. WVSPLAGRT and IGFLIIWV are transported by differentiated intestinal Caco-2 cells. WVSPLAGRT and IGFLIIWV reduce the H2O2-induced oxidative stress in HepG2 cells. WVSPLAGRT and IGFLIIWV modulate the Nrf-2 and iNOS pathways, respectively. Abstract: A preceding paper has shown that a hempseed peptic hydrolysate displays a cholesterol-lowering activity with a statin-like mechanism of action in HepG2 cells and a potential hypoglycemic activity by the inhibition of dipeptidyl peptidase-IV in Caco-2 cells. In the framework of a research aimed at fostering the multifunctional behavior of hempseed peptides, we present here the identification and evaluation of some antioxidant peptides from the same hydrolysate. After evaluation of its diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity, a trans-epithelial transport experiment was performed using differentiated Caco-2 cells that permitted the identification of five transported peptides that were synthesized and evaluated by measuring the oxygen radical absorbance capacity (ORAC), the ferric reducing antioxidant power (FRAP), and the 2, 2-azino-bis-(3-ethylbenzothiazoline-6-sulfonic) acid (ABTS), and diphenyl-2-picrylhydrazyl radical DPPH assays. The most active peptides, i.e. WVSPLAGRT (H2) and IGFLIIWV (H3), were then tested in cell assays. Both peptides were able to reduce the H2 O2 -induced reactive oxygen species (ROS), lipid peroxidation, and nitric oxide (NO) production levels in HepG2 cells, via the modulation of Nrf-2 and iNOS pathways, respectively.